Optimization of hazelnut husk medium for pullulan production by a domestic A. pullulans strain. Issue 3 (1st March 2023) - Akdeniz Oktay, Büşra; Bozdemir, M. Tijen; Ozbas, Z. Yesim
Abstract: Hazelnut husk is one of the most abundant agricultural residue in Turkey. Valorization of this lignocellulosic biomass would provide a promoting alternative for economical production of pullulan. In this study, dried hazelnut husk hydrolysate was used directly as fermentation medium for pullulan production by a domestic strain of Aureobasidium pullulans. The aim of this work was the optimization of some fermentation medium parameters by central composite design using response surface methodology (RSM). The effects of (NH4 )2 SO4 concentration, the volume of concentrated H2 SO4 and the amount of ground hazelnut husk on pullulan production were optimized by RSM. The optimum levels of the fermentation parameters defined as 7.2 gL −1, 2.5 mL and 20 g, respectively. The maximum pullulan and exopolysaccharide concentrations were determined as 74.39 and 75.95 gL −1, respectively in the optimum conditions. Specific growth rate of the strain was found as 0.097 h −1 . FTIR spectral attributes confirmed the structure of pullulan. Thermal decomposition temperature of synthesized pullulan was found as 247.15 °C. This study showed that hazelnut husk was one of the novel substrate for production of the pullulan by A. pullulans AZ-6. No previous work was found to utilize dried hazelnut husk as fermentation medium for pullulan production by A. pullulans .